2013
DOI: 10.1111/myc.12041
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant model for end stage liver disease score predicts posttransplant incidence of fungal infections after liver transplantation

Abstract: Liver transplant recipients are at a significant risk for invasive fungal infections (IFI). This retrospective study evaluated the impact of the pretransplant model for end stage liver disease (MELD) on the incidence of posttransplant IFI in a single centre. From 2004 to 2008, 385 liver transplantations were included, from which 210 transplantations were conducted allocated by Child Turcotte Pugh and 175 were allocated by MELD score. Both groups differed regarding the age of transplant recipients (50.1 ± 10.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
(126 reference statements)
2
23
2
Order By: Relevance
“…The data offer further support for the effectiveness of antifungal prophylaxis in these high-risk settings. In contrast to two recent studies(27, 28), we did not identify pre-transplant model for end stage liver disease (MELD) score to be associated with IFIs. In fact, the IFI rate in patients with MELD score ≥ 30 was only 3.4% and did not significantly differ between targeted and universal groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The data offer further support for the effectiveness of antifungal prophylaxis in these high-risk settings. In contrast to two recent studies(27, 28), we did not identify pre-transplant model for end stage liver disease (MELD) score to be associated with IFIs. In fact, the IFI rate in patients with MELD score ≥ 30 was only 3.4% and did not significantly differ between targeted and universal groups.…”
Section: Discussioncontrasting
confidence: 99%
“…While MELD score of ≥20 is associated with increased risk of bacteremia, LDLT recipients with a MELD score of ≥25 are at increased risk of pneumonia [29, 30]. With regard to systemic mycosis, few studies showed that high MELD score of ≥20 was predictive of IFI [31, 32]. Our result was in agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 83%
“…Risk factors associated with IFI in liver transplant recipients include pre- and postoperative renal failure, retransplantation, substantial intraoperative transfusion of cellular blood products [9], and high Model for End-Stage Liver Disease (MELD) score [2, 12, 13]. As IFIs are associated with mortality rates of 25%–90% [2, 4, 9, 14, 15], antifungal prophylaxis is a rational approach for liver transplant patients considered at high risk.…”
mentioning
confidence: 99%